SKRINING STUNTING DAN PERKEMBANGAN PADA ANAK PRA SEKOLAH DI TK PERTIWI SALEPPA MAJENE: STUNTING AND CHILDREN DEVELOPMENT SCREENING IN PRE SCHOOLS AT TK PERTIWI SALEPPA MAJENE - Eva Yuliani (Jurnal Pengabdian Masyarakat Kesehatan, 2020)
Toddlerhood is a period that is prone to experiencing problems of malnutrition, and development, it is because in infancy the body experiences relatively rapid growth and development compared to other periods. Screening for growth and development of pre-school children is an effort to improve the quality of children. The purpose of this activity is to identify the growth and development of pre-school children. The results of implementing TB / U growth screening (stunting) found the number of children who experienced stunting was 25 people (51%), and normal as many as 24 people (49%), while the developmental examination found 17 people (34.7%) experienced deviations, 11 people (22.4%) experienced doubtful developments and 21 people (42.9%) experienced appropriate developments. Conclusion: more stunting than children who are not stunting and more appropriate level of child development, but there are still children who experience developmental deviations.